Homotopic Commissural Projections of Area Prostriata in Rat and Mouse: Comparison With Presubiculum and Parasubiculum - Chen, Chang-Hui; Hu, Jin-Meng; Chen, Sheng-Qiang; Liu, Shi-Ming; Ding, Song-Lin (Frontiers in Neural Circuits, 2020)
Area prostriata in primate has recently been found to play important roles in rapid detection and processing of peripheral visual, especially fast-moving visual information. The prostriata in rodent was not discovered until recently and its connectivity is largely unknown. As a part of our efforts to reveal brain-wide connections of the prostriata in rat and mouse, this study focuses on its commissural projections in order to understand the mechanisms underlying interhemispheric integration of information, especially from peripheral visual field. Using anterograde, retrograde and Cre-dependent tracing techniques, we found a unique commissural connection pattern of the prostriata: layers 2-3 of the prostriata in both hemispheres form strong homotopic commissural connections with few heterotopic projections to bilateral medial entorhinal cortex. This projection pattern is in sharp contrast to that of the presubiculum and parasubiculum, two neighbor regions of the prostriata. The latter two structures project very strongly to bilateral medial entorhinal cortex and to their contralateral counterparts. Our results suggest the prostriata is a distinct anatomical structure from the presubiculum and parasubiculum and probably plays differential roles in interhemispheric integration and the balancing of spatial information.